Effective Classroom Management: Student Behavior Management Strategies in the Digital Era - Yatha Yuni; Ahmad Jauhari Hamid Ripki; Masrum Masrum; Ismail Akbar Brahma; Arida Erwianti (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to explore effective classroom management and student behavior management strategies in the digital era. Using a qualitative approach and descriptive analysis, data was collected from 16 selected articles from Google Scholar (2012-2024). The findings indicate that establishing clear rules, utilizing technology, involving parents, and developing social skills are key strategies in creating a positive learning environment. By leveraging digital applications and platforms, teachers can enhance student engagement and reduce negative behavior. The implications of this research emphasize the need for teacher training and collaboration with parents to support behavior management. This study is expected to contribute to the development of better educational practices in the digital era and open opportunities for further research on student behavior management in broader contexts.